OVERVIEW OF TELEDIAGNOSIS IN BRAZIL FROM 2016 TO THE FIRST WAVE OF THE COVID-19 PANDEMIC - Jandre Reis, Felipe José; de Castro Brasil Pinheiro , Clarissa; Martin Bandeira, Pâmela; Gaspar Fernandes, Lívia; Tirotti Saragiotto, Bruno (Cadernos ESP, 2023)
Telemedicine, including telediagnosis, must be recognized as an alternative to overcome geographical barriers, provide patients with access to health care and ensure continuity of follow-up. The aim of this study was to quantify the number of telediagnosis from 2016 to the first wave of the COVID-19 pandemic in Brazil. This study is a secondary analysis of data from the Brazilian Ministry of Health. The main outcomes were: total number of telediagnoses performed, mean time to telediagnosis notification; the distribution of states and municipalities with the highest number of telediagnosis and the health specialties that performed telediagnosis the most. A total of 4,010,087 telediagnoses with irregular distribution were identified (59.5% in Minas Gerais, 29.4% in Santa Catarina, 3.3% in Ceará and 2.2% in Bahia). At the beginning of COVID cases in Brazil, there was a reduction in telediagnosis, being 12% in February, 41% in March, 81% in April, 80% in May and 76% in June. Brazil presented an irregular distribution of telediagnoses in the different states. During the first wave of the COVID-19 pandemic, a significant reduction in the number of telediagnoses was observed.